Political consumerism and the decline of class politics in Western Europe. (October 2013) - Ferrer-Fons, Mariona; Fraile, Marta
This article examines whether social class influences the likelihood of engaging in political consumerism in Western Europe. Political consumption is the intentional buying or abstention from buying (boycotting) specific products for political, ethical, or ecological reasons. The interest in analyzing political consumerism lies in substantive and theoretical reasons. First, it is a widespread but not very adequately studied form of noninstitutionalized political participation. Second, various theories claim that class is an inadequate category for explaining political behavior. According to the postmodern theory of social stratification, patterns of consumption are among the key factors that define the new status communities, thus breaking with the traditional logic of social classes. Along the same lines, individualization theory suggests that in contemporary societies, individuals are free to continuously redefine their identity and choose the lifestyle they prefer. We argue that the study of political consumption offers a particularly appropriate case for testing the empirical plausibility of the hypothesis of the 'decline of class politics'. Multilevel analysis using European Social Survey data reveals, contrary to the above-mentioned postulates, that social class strongly affects the likelihood of being one's a political consumer.